Authority Of The Police In The Eradication Of Criminal Acts Of Terorism According To Law No. 15 Of 2003 - Melky Sidhek Gultom (Journal of Law Science, 2020)
Terrorism is a terrible threat to every country in the world, destroying state stability, security functions, socio-cultural, economic, political and can even shake various religious parties. As a state of law, Indonesia has an obligation to protect the rights of its citizens. Through Law Number 15 of 2003 concerning the Eradication of Criminal Acts of Terrorism and Law Number 2 of 2002 concerning the Police, terrorists must be eradicated to their roots to create security, peace and social welfare for the community. For this reason, the authority of the Police in eradicating criminal acts of terrorism is to establish the Special Datasemen 88 Anti-Terror as a special elite force to deal with terrorist acts and their eradication.The problems discussed in this thesis are: First, how is the regulation of criminal acts of terrorism according to Law Number 15 of 2003 concerning the eradication of criminal acts of terrorism? Second, how is the authority of the Police in eradicating criminal acts of terrorism, the method used in this thesis is the normative juridical approach, the data source used is secondary data through library research data collection tools and through qualitative data. The conclusion in this thesis, that the authority of the Police in eradicating criminal acts of terrorism refers to the various efforts taken, the application of legal regulations and sanctions against terrorist actors, as well as implementing penal and non-penal policies, UUPTPT applies retroactive law enforcement to cases cases that have passed before the emergence of the PTPT Law which regulates it, the authority of the Police to provide protection, protection, and law enforcement for the community and involves the role of the Special Detachment 88 Anti-Terror as the forefront in carrying out prosecutions and arrests. It is recommended for the National Police to carry out surveillance of urban and rural residents for the role of the Community Police (Polmas) which is very important as an early detection of the development of the local community.